Tinjauan Penegakan Hukum dan Penerapan Sanksi terhadap Pelaku Pencabulan Anak Dibawah Umur - Nispa Octapiani; Meilisya Salsabila; Muhammad Fajar Hidayat (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Child sexual abuse is a very complex and sensitive issue in society. The rapid development of society and the increase in crime have an impact on interactions that often violate the law, creating a sense of security, peace and order in society. The crime of sexual abuse of minors is committed by adults and children themselves, and is an important problem to be discussed. The purpose of this study is 1. to find out the efforts made by law enforcers in overcoming sexual abuse of minors 2. to find out how the application of sanctions against perpetrators of criminal acts of sexual abuse of minors. This research uses normative juridical methods, namely legal research conducted on legal norms contained in laws and regulations relating to the criminal offense of child abuse and the provisions of the law. The results of research and discussion show that law enforcement efforts in overcoming child abuse include several steps, namely: conducting investigations and investigations, prosecution of perpetrators, analyzing and considering in deciding cases, conducting supervision and monitoring to correctional institutions and focusing on victim protection with strict law enforcement. The application of criminal sanctions against perpetrators of child abuse through several stages, namely the process of investigation and investigation of investigation and prosecution.